Imants Tillers : journey to nowhere = Imants Tillers : celojums uz nekurieni - Tillers, Imants, 1950-; Ansone, Elita, 1964-; Williams, Marni; Svilane, Terēze; Lešinska-Geibere, Leva; Mikelsons, Valts; Latvijas Nacionālais mākslas muzejs ([Sydney, Australia] : Power Publications, University of Sydney, 2018)
"For the renowned artist Imants Tillers, whose career spans more than four decades of prolific creative practice, this ̀journey to nowhere' is neither a homecoming nor a departure, but a fertile and thought-provoking meeting of worlds. The son of Latvian parents who were displaced during the Second World War, Tillers was born in Sydney, Australia, where he would speak Latvian before English and long feel the pull of a distant culture. Displacement, diaspora and an awareness of the complex weave of cultures marks all his work, from his experiments with installation in the 1970s and trailblazing appropriations in the 1980s to the holistic system of modular (canvasboard) paintings that number 108,224 today. With contributions from Elita Ansone, Graham Coulter-Smith, Mark Ledbury, Ian McLean and Tillers himself, this publication traces the artist's career through his most formative journeys, be they physical, collaborative or philosophical. As the work crosses vast physical, metaphysical and mytho-poetic terrain, our authors find themselves in Karosta, Papunya, Cooma and many distant art-historical shores along the way. From this complex odyssey emerges a distinct and creative vision, that of a visual philosopher who identifies as an outsider in the city of his birth and visitor in his homeland."--Back cover.
Catalogue accompanies a major exhibition of works by Imants Tillers held at the Latvian National Museum of Art, 7 July-30 September 2018.
Includes bibliographical references.
Parallel text in Latvian and English.
Keywords: Tillers, Imants, -- 1950- -- Exhibitions; Painting, Australian -- 20th century -- Exhibitions; Art, Australian -- Exhibitions; Painting, Australian -- 21st century -- Exhibitions; Australian; Exhibition catalogs